The Urban & Economic Characteristics of Major Arab Cities in the Nineteenth Century, through the French Travelers Observations - Cairo as a Model - hassad, Abdessamed; Grine, Mouloud (Milev Journal of Research and Studies, 2021)
The trip is considered as one of the most important historical sources that supports the researcher with an abundant scientific materials, especially since the travelers have recorded all the observations they saw in the areas they visited. The French travelersare ones of the pioneers of the traveler to the East, there are several factors that make them to be in this trip. In the forefront of which is the religious factor in the framework of what is known as the Christian pilgrimage in which it passes through several stations, including the Cairo station, which contains Christian sanctuaries. From there they continue their pilgrimage trip to the Levant .The nineteenth century witnessed a significant increase in French trips, especially that France got privileges fromThe Ottoman Empire to protect theorthodoxe as well as their holy places, and thus the abundance of French writings, through which we tried to find out the impressions that these travelers make for Arab Islamic cities, and we choose Cairo as one of the most prominent Arab cities at that time, as well as being one of the most prominent stations in French travel.We relied on the descriptive historical method while writing this reaserch paper